Comparison of social and sociodemographic characteristics and treatment goals of persons with alcohol versus drug use disorders: Result from a national census of inpatients in specialized treatment for substance use. (June 2021) - Andersson, Helle Wessel; Lilleeng, Solfrid E.; Ose, Solveig Osborg
Highlights: A national census of patients in residential substance use treatment. We compared inpatients with primary alcohol use disorders vs. drug use disorders. Patients with drug use disorders were more likely sociodemographic disadvantaged. Patients with drug use disorders more likely had poor friend relationships. Treatment goal differences disappeared when adjusted for sociodemographic variables. Abstract: Introduction: We examined differences in social and sociodemographic characteristics and treatment goals between people with primary alcohol use disorder (AUD) versus those with a primary drug use disorder receiving inpatient treatment for a substance use disorder (SUD). Methods: A national census utilizing a cross sectional design included 56 of 60 specialized inpatient SUD treatment clinics in Norway and all patients receiving treatment on a specific date (responserate = 70% ). Data on substance use, social and sociodemographic characteristics, and patient-reported treatment goals were collected. Patients were classified as having primary AUD or a drug use disorder based on the main SUD diagnosis relevant to the treatment episode. Results: The analytic sample included 1093 patients. Patients with primary AUD (n = 362) were more often older, had a higher educational level and income from work, and lived in permanent housing compared with patients with a drug use disorder (n = 731). Patients with AUD were more likely to have good relationships with friends. The higher frequency of reported reduced substance use (versus quitting substance use) as the treatment goal among AUD patients disappeared when controlled for sociodemographic factors. Conclusions: Knowledge about the different characteristics of inpatients with AUD versus a drug use disorder is relevant when conducting research involving the SUD treatment population and for facilitating treatment. The lower frequency of perceived support from friends among patients with a drug use disorder suggests a need for targeted efforts in (re)building supportive social relationships for inpatients being treated for SUD.